Steganographic scheme to avoid statistical Steganalysis - جمال احمد عثمان (College of Education for Women, 2019)
significant bits either in the spatial domain or frequency domain sequentially or pseudo randomly through the cover media (Based on this fact) statistical Steganalysis use different techniques to detect the hidden message, A proposed method is suggested of a stenographic scheme a hidden message is embedded through the second least significant bits in the frequency domain of the cover media to avoid detection of the hidden message through the known statistical Steganalysis techniques.